Contractors Selection of Warehouse Construction using AHP Method at PT. Bangun Eka Logitama - Wiyatno, Tri Ngudi; Sutrisno, Arif; Riandani, Andini Putri; Khofiyah, Nida An; Anandartiana, Wawan Gunawan (Proceeding International Pelita Bangsa, 2023)
PT. Bangun Eka Logitma (PT. BEL) is a company engaged as a provider of warehousing services in Indonesia. PT. BEL is currently expanding its assets by building a new warehouse which will then be rented out to its customers. The construction of the warehouse was carried out by the Contractor where there were 4 prospective Contractors for this project. The purpose of this research is to determine the right contractor for the warehouse construction. The method used in the selection of contractors is the Analytical Hierarchy Process (AHP) method. The criteria used in this study consisted of 4 criteria, Task Performance, Contextual Performance, Price, and Network. While the 4 prospective contractors are PT. Mitralanggeng Prama Construction, PT. Sukses Trakindo, PT. Muri Agung Abadi & PT. Gerbang Sarana Baja. This study obtains the proportion of each criterion task performance = 0.339, price = 0.300, contextual performance = 0.293, and network = 0.68. Based on the criteria used in the contractor selection using the AHP method, the contractor with the highest score was PT. Muri Agung Abadi = 0.460, the second highest is PT. Sukses Trakindo = 0.351, the third highest is PT. Mitralanggeng Prama Construction = 0.118, and PT. Gerbang Sarana Baja have the lowest score = 0.071. So that the contractor chosen in the construction of PT. BEL is PT. Muri Agung Abadi.